Chaoyang Bridge, China: a double-deck cable-stayed bridge with corrugated steel webs. Issue 1 (7th August 2018) - Deng, Wenqin; Zhang, Jiandong; Liu, Duo; Hu, Jun; Hu, Fangjian; Zhong, Zhibing
Abstract : Completed in 2016, Chaoyang Bridge in China is the world's first double-deck composite girder cable-stayed bridge with corrugated steel webs. It provides a dual four-lane highway above with cantilevered footways and cycleways below. As described in this paper, the bridge features several design innovations. These include the first use of corrugated steel webs for a cable-stayed double-deck crossing, new cable anchorage technology and a building information modelling management system to resolve structural defects.